KOLABORASI KEPOLISIAN DENGAN MASYARAKAT DALAM RANGKA MENGANTISIPASI PENCURIAN KENDARAAN BERMOTOR RODA DUA - Lubby, Intan Widyana (Universitas Panca Marga, 2024)
This research aims to analyze the collaboration between the Taman Sidoarjo police and the community in anticipating cases of theft. The analytical method used in this research is a qualitative method carried out by in-depth interviews. The results of the research show that the increase in theft cases is really disturbing the community. People's security and comfort are disturbed by the fear of losing their motorized vehicles. Taman Sidoarjo Police collaborates with the community to overcome theft by conducting socialization and outreach programs, forming community security groups, security training, giving prizes for information, using online reporting, and joint patrols. Factors causing crime include public unawareness, economic factors, and environmental influences. The research also discusses concrete efforts by the Taman Sidoarjo Police, such as prevention programs, responses to community reports, and adaptation to crime trends. This research contributes to understanding the effectiveness of police cooperation in dealing with criminal acts of theft of two-wheeled motorized vehicles, and provides recommendations for further improvements to increase security in the area